Collaborative Multi-racial Post-election Survey (CMPS), 2012 - Frasure-Yokley, Lorrie ([Verlag nicht ermittelbar], 2020)
The 2012 Collaborative Multi-racial Post-election Survey (CMPS) was a national survey of registered voters from three groups: White non-Hispanic adults, Black non-Hispanic adults, and English and Spanish speaking Hispanic adults. The survey was conducted between November 16, 2012 and November 26, 2012 in both English and Spanish, and examined individual's experiences with voting and attitudes about social and economic issues prominent in the 2012 election. The 2012 CMPS included 37 items dealing with sociopolitical attitudes, mobilization political activity, advertising exposure and neighborhood context as well as three embedded survey experiments. Additionally, there were 15 items that capture demographic information, including: age, ancestry, birthplace, education, ethnicity, Latin American racial descriptors, skin color, marital status, household size, religiosity, gender, sexual orientation, internet usage, and residential context. In addition to the survey and demographic data, the 2012 CMPS also included shifted latitude and longitude values for each respondent. This allowed for more nuanced modeling with regard to contextual variables at the tract, city, county, Metropolitan Statistical Area (MSA) level, and Congressional district. Geographic information below state level is only available within the restricted-use data file for this collection.